In the pursuit of new social neurons. Neurogenesis and social behavior in mice: A systematic review - García-Gómez, Lydia; Castillo-Fernández, Iker; Perez-Villalba, Ana (Frontiers in Cell and Developmental Biology, 2022)
Social behaviors have become more relevant to our understanding of the human nervous system because relationships with our peers may require and modulate adult neurogenesis. Here, we review the pieces of evidence we have to date for the divergence of social behaviors in mice by modulation of adult neurogenesis or if social behaviors and the social environment can drive a change in neurogenic processes. Social recognition and memory are deeply affected by antimitotic drugs and irradiation, while NSC transgenic mice may run with lower levels of social discrimination. Interestingly, social living conditions can create a big impact on neurogenesis. Social isolation and social defeat reduce the number of new neurons, while social dominance and enrichment of the social environment increase their number. These new “social neurons” trigger functional modifications with amazing transgenerational effects. All of these suggest that we are facing two bidirectional intertwined variables, and the great challenge now is to understand the cellular and genetic mechanisms that allow this relationship to be used therapeutically.